The mitochondrial genome of Dendrobaena tellermanica Perel, 1966 (Annelida: Lumbricidae) and its phylogenetic position - S. V. Shekhovtsov; G. V. Vasiliev; R. Latif; T. V. Poluboyarova; S. E. Peltek; I. B. Rapoport (Вавиловский журнал генетики и селекции)
Earthworms are an important ecological group that has a significant impact on soil fauna as well as plant communities. Despite their importance, genetic diversity and phylogeny of earthworms are still insufficiently studied. Most studies on earthworm genetic diversity are currently based on a few mitochondrial and nuclear genes. Mitochondrial genomes are becoming a promising target for phylogeny reconstruction in earthworms. However, most studies on earthworm mitochondrial genomes were made on West European and East Asian species, with much less sampling from other regions. In this study, we performed sequencing, assembly, and analysis of the mitochondrial genome of Dendrobaena tellermanica Perel, 1966 from the Northern Caucasus. This species was earlier included into D. schmidti (Michaelsen, 1907), a polytypic species with many subspecies. The genome was assembled as a single contig 15,298 bp long which contained a typical gene set: 13 protein-coding genes (three subunits of cytochrome c oxidase, seven subunits of NADH dehydrogenase, two subunits of ATP synthetase, and cytochrome b), 12S and 16S ribosomal RNA genes, and 22 tRNA genes. All genes were located on one DNA strand. The assembled part of the control region, located between the tRNA-Arg and tRNA-His genes, was 727 bp long. The control region contained multiple hairpins, as well as tandem repeats of the AACGCTT monomer. Phylogenetic analysis based on the complete mitochondrial genomes indicated that the genus Dendrobaena occupied the basal position within Lumbricidae. D. tellermanica was a rather distant relative of the cosmopolitan D. octaedra, suggesting high genetic diversity in this genus. D. schmidti turned out to be paraphyletic with respect to D. tellermanica. Since D. schmidti is known to contain very high genetic diversity, these results may indicate that it may be split into several species.